Anti-microbial activity of chrysomycin a produced by streptomyces sp. against mycobacterium tuberculosis - Balaji, Muralikrishnan; Dan, Vipin Mohan; Joseph, Vinodh; Jamsheena, Vellekkatt; Ramachandran, Ranjit; Thomas, Sabu; Dastager, Syed Gulam; Kumar, K. Santhosh; Lankalapalli, Ravi Shankar; Kumar, R. Ajay (RSC Advances, 2017)
Limited efficacy of the BCG (Bacillus Calmette–Guérin) vaccine against adult tuberculosis and the emergence of resistance to existing anti-tuberculosis drugs compel discovery of novel antibiotics against Mycobacterium tuberculosis. Actinomycetes are still an attractive platform for the discovery of new antimicrobials, especially from untapped natural hotspots, despite the belief that they are an exhausted resource after repeated re-discoveries. Herein we report the isolation and identification of chrysomycin A from an actinomycete isolated from a coastal area in Kerala. We show for the first time that it has antimycobacterial activity. It was found to be bactericidal to planktonic and intracellular M. tuberculosis with an MIC of 3.125 μg mL⁻¹; it is non-hemolytic and has negligible cytotoxicity. The actinomycete that produces chrysomycin A was found to be a Streptomyces sp. through 16S rRNA gene sequencing.